Additive manufacturing of copper vertical interconnect accesses by laser processing. Issue 1 (2021) - Overmeyer, Ludger; Olsen, Ejvind; Hoffmann, Gerd-Albert
Abstract : This paper introduces a new manufacturing process for vertical interconnect accesses (VIA). In contrast to industrially established VIA metallization technologies, the presented approach takes place without any chemical plating by combining copper ink and epoxy insulator coating with CO2 laser processing for VIA drilling and copper ink sintering. The minimum VIA resistances are less than 50 mΩ, fitting the theoretically calculated value. A laboratory application scenario testing a 10 × 10 contact pad array with a pitch of 800 µm successfully demonstrates routing across five printed metallization layers, including 128 blind and 112 buried VIA.